The Effectiveness of PBL Problems from Students and Tutors Perspectives - Savitri Shitarukmi; Siti Rokhmah Projosasmito; Herma Roebertsen (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2017)
Background: PBL problems are used as a starting point to students in attaining learning objectives. Students are expected to discuss the problems according the principles of collaborative learning, constructive learning, contextual learning, and self-directed learning. A continuous monitoring, evaluating, and improving the PBL problems should be done systematically. Nevertheless, the problems are lacking monitoring and evaluation. The aim of this study is to evaluate the effectiveness of PBL problem by providing an evaluation tool. The evaluation involved students and tutors.Method: A survey by using questionnaire based on six factors of an effective PBL problem was conducted to obtain students and tutors perception towards the effectiveness of 6 PBL problems used in tutorial session. The questionnaire for each scenario distributed to four randomly selected group tutorials (total samples per scenario is 40 students and four tutors). The perceptions were then analysed by using descriptive statistic. Four open ended questions included in the questionnaire were used to get better understanding and explanation of quantitative result.Results: A total of 198 (82.5% response rate) students and 23 (95% response rate) tutors filled the questionnaire. Students and tutors gave their score for the overall quality of each PBL problems. Some differences among students and tutors in rating the overall quality on each problem were found. The strength and the weakness of each problem were also obtained from students’ and tutors’ rate for the six factors in the questionnaire. Each group of participants had their own concern regarding the most important factor for an effective PBL problem.Conclusion: The result of this evaluation could reflect the effectiveness of PBL problems in achieving students’ learning objectives from different viewpoints: students and tutors. This valuable information can be used by problem designers and their institutions to monitor and improve the quality of PBL problems continuously.